Linking consumer prices to wholesale prices and to money supply: some cointegration experiments for the case of Greece - Πάλλης Δημήτριος; Κατσούλη Ελένη (SPOUDAI Journal of Economics and Business, 2003)
The purpose of this paper is to investigate and measure the extent to which consumer prices are affected by changes in wholesale prices and in money supply. The data used in the investigation are monthly, covering the period from 1973:1 to 2000:11, and refer to consumer price indexes, finished products wholesale price index, and Ml money supply index. Multivariate cointegration methods are used in order to investigate the transfer of changes from wholesale prices and money supply to consumer prices, or in other words to test the existence or not of a long-term equilibrium relationship between the three variables. The paper concludes that long-term relationships exist between consumer prices and money supply and between wholesale prices and money supply. Thus, error correction models (ECM) are developed and estimated using the restricted VAR methodology. JEL Classification: E31, E52